A structural model of healthcare personnel readiness for telerehabilitation in Malaysian healthcare institutions - Jafni, Tiara Izrinda (2020)
A structural model of healthcare personnel readiness for telerehabilitation in Malaysian healthcare institutionsTelerehabilitation is a modern innovation used for rehabilitation services. Evidence in favor of readiness among healthcare personnel for telerehabilitation is limited. Since “readiness” is a crucial prerequisite to the successful implementation of an innovation, studying healthcare personnel readiness for telerehabilitation is mandatory to gain a better understanding of the relationships among the factors. Meanwhile, the explored factors in telerehabilitation readiness research remain on the surface without a clear direction. There are no existing studies that explore and analyze the relationship between these factors. To fill this gap, identifying factors influencing the readiness of healthcare personnel for telerehabilitation and a model that can show the interaction of those factors are needed. This research aims to identify the relationship of factors affecting the readiness of healthcare personnel for telerehabilitation. A positivist qualitative approach is adopted using the case studies of Malaysian healthcare institutions in the rehabilitation sector. In doing so, focus group interview sessions with healthcare personnel were conducted for both pilot and primary case studies. Through the employment of the content analysis technique, the data collection analysis was divided into two phases. The first phase involved a within-case analysis and cross-case analysis while the second phase involved the verification of the factors with the healthcare personnel. Additionally, the Interpretive Structural Modeling (ISM) approach was conducted to identify the most influential factors. Finally, the model of contextual relationships of healthcare personnel readiness for telerehabilitation was formed consisting of the relationship of factors. The factors were also classified as either driver or barrier categories. The driver involves the factors of awareness, comfort, satisfaction and willingness, learnability, and e-healthcare knowledge. Furthermore, the barrier factors consist of financial/cost, planning, resistance to change, connectivity, skills, hardware and software, and training. A clear understanding of these factors will help healthcare institutions to better prioritize and manage their healthcare personnel efficiently and effectively for telerehabilitation. On the other hand, the development of a structured model will help healthcare institutions to understand the relationship between the factors closely. Important factors concerning the high drivingTelerehabilitation is a modern innovation used for rehabilitation services. Evidence in favor of readiness among healthcare personnel for telerehabilitation is limited. Since “readiness” is a crucial prerequisite to the successful implementation of an innovation, studying healthcare personnel readiness for telerehabilitation is mandatory to gain a better understanding of the relationships among the factors. Meanwhile, the explored factors in telerehabilitation readiness research remain on the surface without a clear direction. There are no existing studies that explore and analyze the relationship between these factors. To fill this gap, identifying factors influencing the readiness of healthcare personnel for telerehabilitation and a model that can show the interaction of those factors are needed. This research aims to identify the relationship of factors affecting the readiness of healthcare personnel for telerehabilitation. A positivist qualitative approach is adopted using the case studies of Malaysian healthcare institutions in the rehabilitation sector. In doing so, focus group interview sessions with healthcare personnel were conducted for both pilot and primary case studies. Through the employment of the content analysis technique, the data collection analysis was divided into two phases. The first phase involved a within-case analysis and cross-case analysis while the second phase involved the verification of the factors with the healthcare personnel. Additionally, the Interpretive Structural Modeling (ISM) approach was conducted to identify the most influential factors. Finally, the model of contextual relationships of healthcare personnel readiness for telerehabilitation was formed consisting of the relationship of factors. The factors were also classified as either driver or barrier categories. The driver involves the factors of awareness, comfort, satisfaction and willingness, learnability, and e-healthcare knowledge. Furthermore, the barrier factors consist of financial/cost, planning, resistance to change, connectivity, skills, hardware and software, and training. A clear understanding of these factors will help healthcare institutions to better prioritize and manage their healthcare personnel efficiently and effectively for telerehabilitation. On the other hand, the development of a structured model will help healthcare institutions to understand the relationship between the factors closely. Important factors concerning the high driving and dependence power can be identified by understanding the relationship of factors. and dependence power can be identified by understanding the relationship of factors.